Lawyer CEOs - Henderson, M. Todd; Hutton, Irena; Jiang, Danling; Pierson, Matthew (Journal of Financial and Quantitative Analysis, 2025)
Abstract We study when CEOs with legal expertise are valuable for firms. In general, lawyer CEOs are negatively associated with frequency and severity in employment civil rights, contract, labor, personal injury, and securities litigation. This effect is partly induced by the CEO’s management of litigation risk and reduction in other risky policies. Lawyer CEOs are further associated with an increase in gatekeepers providing additional legal oversight and a decrease in innovative activities with high litigation risk. Lawyer CEOs are more valuable during periods of enhanced compliance requirements and regulatory pressure and in industries with high litigation risk or better growth opportunities.